Assessing the developmental patterns of visitation on prison misconduct: do visitation patterns matter?. Issue 2 (2nd April 2020) - Cihan, Abdullah; Reidy, Thomas J; Sorensen, Jon; Chism, Kimberly A.
ABSTRACT: Using a sample of 1, 502 male inmates incarcerated in a correctional facility in a Northwestern state between March 2010 and June 2017 for a minimum of 3 years, the current study examines: 1) The heterogeneous nature of visitation experiences and prison misconduct over time; 2) The long-term effects of distinct visitation patterns on prison misconduct; and 3) The predictive utility of identified visitation patterns along with certain inmate characteristics in predicting distinct prison misconduct patterns. Results from trajectory and multivariate analyses identified five visitation and four misconduct groups. The findings suggest that high and early levels of visitation groups yielded a lower likelihood of persistent disciplinary offending. Additionally, age, criminal history, gang affiliation, mental health, and custody status were related to persistent misconduct. Visitation is an important determinant of inmate misconduct, which emphasizes the need for social support as early as possible during an inmate's prison term. Additional implications are discussed.